Measuring the welfare gain from personal computers: A macroeconomic approach - Karen A. Kopecky; Jeremy Greenwood (Federal Reserve Bank of Atlanta, 2011)
The welfare gain to consumers from the introduction of personal computers is estimated here. A simple model of consumer demand is formulated that uses a slightly modified version of standard preferences. The modification permits marginal utility, and hence total utility, to be finite when the consumption of computers is zero, implying that the good won't be consumed at a high enough price. It also bounds the consumer surplus derived from the product. The model is calibrated and estimated using standard national income and product account data. The welfare gain from the introduction of personal computers is in the range of 2 percent to 3 percent of consumption expenditure.
Keywords: E01; E21; O33; O47; 330; compensating variation; computers; electricity; equivalent variation; technological progress; Tornqvist price index; welfare gain